A concept of dual-responsive prodrugs based on oligomerization-controlled reactivity of ester groups: an improvement of cancer cells versus neutrophils selectivity of camptothecin - Klemt, Insa; Reshetnikov, Viktor; Dutta, Subrata; Bila, Galyna; Bilyy, Rostyslav; Cuartero, Itziar Cossío; Hidalgo, Andrés; Wünsche, Adrian; Böhm, Maximilian; Wondrak, Marit; Kunz-Schughart, Leoni A.; Tietze, Rainer; et al. (RSC Medicinal Chemistry, 2024)
Many known chemotherapeutic anticancer agents exhibit neutropenia as a dose-limiting side effect. In this paper we suggest a prodrug concept solving this problem for camptothecin (HO-cpt). The prodrug is programmed according to Boolean “AND” logic. In the absence of H2O2 (trigger T1), e.g. in the majority of normal cells, it exists as an inactive oligomer. In cancer cells and in primed neutrophils (high H2O2), the oligomer is disrupted forming intermediate (inactive) lipophilic cationic species. These are accumulated in mitochondria (Mit) of cancer cells, where they are activated by hydrolysis at mitochondrial pH 8 (trigger T2) with formation of camptothecin. In contrast, the intermediates remain stable in neutrophils lacking Mit and therefore a source of T2. In this paper we demonstrated a proof-of-concept. Our prodrug exhibits antitumor activity both in vitro and in vivo, but is not toxic to normal cell and neutrophils in contrast to known single trigger prodrugs and the parent drug HO-cpt.
CRIS-Team Scopus Importer:2024-04-19

A Conserved Kinase-Based Body-Temperature Sensor Globally Controls Alternative Splicing and Gene Expression - Haltenhof, Tom; Kotte, Ana; De Bortoli, Francesca; Schiefer, Samira; Meinke, Stefan; Emmerichs, Ann-Kathrin; Petermann, Kristina Katrin; Timmermann, Bernd; Imhof, Petra; Franz, Andreas; Loll, Bernhard; Wahl, Markus C.; et al. (Molecular Cell, 2020)
Homeothermic organisms maintain their core body temperature in a narrow, tightly controlled range. Whether and how subtle circadian oscillations or disease-associated changes in core body temperature are sensed and integrated in gene expression programs remain elusive. Furthermore, a thermo-sensor capable of sensing the small temperature differentials leading to temperature-dependent sex determination (TSD) in poikilothermic reptiles has not been identified. Here, we show that the activity of CDC-like kinases (CLKs) is highly responsive to physiological temperature changes, which is conferred by structural rearrangements within the kinase activation segment. Lower body temperature activates CLKs resulting in strongly increased phosphorylation of SR proteins in vitro and in vivo. This globally controls temperature-dependent alternative splicing and gene expression, with wide implications in circadian, tissue-specific, and disease-associated settings. This temperature sensor is conserved across evolution and adapted to growth temperatures of diverse poikilotherms. The dynamic temperature range of reptilian CLK homologs suggests a role in TSD.
Created from Fastlane, Scopus look-up
Keywords: alternative splicing; body temperature; CIRBP; CLK kinase; sex determination; SR proteins; temperature sensing; TSD

A Networks Approach to Modeling Enzymatic Reactions - Imhof, Petra (Methods in Enzymology, 2016)
Modeling enzymatic reactions is a demanding task due to the complexity of the system, the many degrees of freedom involved and the complex, chemical, and conformational transitions associated with the reaction. Consequently, enzymatic reactions are not determined by precisely one reaction pathway. Hence, it is beneficial to obtain a comprehensive picture of possible reaction paths and competing mechanisms. By combining individually generated intermediate states and chemical transition steps a network of such pathways can be constructed. Transition networks are a discretized representation of a potential energy landscape consisting of a multitude of reaction pathways connecting the end states of the reaction. The graph structure of the network allows an easy identification of the energetically most favorable pathways as well as a number of alternative routes.
CRIS-Team Scopus Importer:2020-02-18
Keywords: Energy landscape; Hydrolysis; Path sampling; QM/MM; Transition network

Base flip in DNA studied by molecular dynamics simulations of differently-oxidized forms of methyl-cytosine - Helabad, Mahdi Bagherpoor; Kanaan, Natalia; Imhof, Petra (International Journal of Molecular Sciences, 2014)
Distortions in the DNA sequence, such as damage or mispairs, are specifically recognized and processed by DNA repair enzymes. Many repair proteins and, in particular, glycosylases flip the target base out of the DNA helix into the enzyme's active site. Our molecular dynamics simulations of DNA with intact and damaged (oxidized) methyl-cytosine show that the probability of being flipped is similar for damaged and intact methyl-cytosine. However, the accessibility of the different 5-methyl groups allows direct discrimination of the oxidized forms. Hydrogen-bonded patterns that vary between methyl-cytosine forms carrying a carbonyl oxygen atom are likely to be detected by the repair enzymes and may thus help target site recognition. © 2014 by the authors; licensee MDPI, Basel, Switzerland.
CRIS-Team Scopus Importer:2020-02-18
Keywords: Base flip; DNA damage; DNA recognition; Molecular dynamics simulations

Catalytic mechanism of DNA backbone cleavage by the restriction enzyme EcoRV: A quantum mechanical/molecular mechanical analysis - Imhof, Petra; Fischer, Stefan; Smith, Jeremy C. (Biochemistry, 2009)
Endonucleases, such as the restriction enzyme EcoRV, cleave the DNA backbone at a specific recognition sequence. We have investigated the catalytic mechanism of backbone phosphodiester hydrolysis by the restriction enzyme EcoRV by means of hybrid quantum mechanical/molecular mechanical calculations. An exhaustive computation of different reaction pathways is performed, thus generating a network of pathways. Comparison of the computed (AM1d/MM) enzymatic reaction pathways with an analogous mechanism for small-molecule model systems [AM1/d and B3LYP/6-31 + + G(d,p)] reveals that the transition barriers for associative hydrolysis, which is more probable in the model systems, are not lowered by the enzyme. Instead, a reaction mechanism which has mostly dissociative character is more likely. The protein environment is tuned to significantly electrostatically stabilize the transition state structures. The direct catalytic impact of essential residues is determined: The magnesium metal ion activates a water molecule, thus facilitating protonation of the leaving group. A reduction of the coordination number of the magnesium metal ion from six to four upon the positioning of the attacking water molecule explains why larger metal ions, such as calcium, are not catalytically active. The nucleophile is generated by the transfer of a proton from the attacking water molecule to a carboxylic oxygen atom of aspartate 90. The catalytic effect of lysine 92 involves proper positioning of the scissile phosphate group and, more importantly, stabilization of the metaphosphate intermediate in an orientation optimal for attack of the nucleophile. ©2009 American Chemical Society.
CRIS-Team Scopus Importer:2020-02-18

Comparison of Empirical Zn2+ Models in Protein–DNA Complexes - Volkenandt, Senta; Imhof, Petra (Biophysica, 2023)
Zinc ions are the second most abundant ions found in humans. Their role in proteins can be merely structural but also catalytic, owing to their transition metal character. Modelling their geometric–coordination versatility by empirical force fields is, thus, a challenging task. In this work, we evaluated three popular models, specifically designed to represent zinc ions with regard to their capability of preserving structural integrity. To this end, we performed molecular dynamics simulations of two zinc-containing protein–DNA complexes, which differed in their zinc coordination, i.e., four cysteines or two cysteines and two histidines. The most flexible non-bonded 12-6-4 Lennard–Jones-type model shows a preference for six-fold coordination of the Zn (Formula presented.) -ions in contradiction to the crystal structure. The cationic dummy atom model favours tetrahedral geometry, whereas the bonded extended zinc AMBER force field model, by construction, best preserves the initial geometry of a regular or slightly distorted tetrahedron. Our data renders the extended zinc AMBER force field the best model for structural zinc ions in a given geometry. In more complicated cases, though, more flexible models may be advantageous.
CRIS-Team Scopus Importer:2023-11-24
Keywords: molecular dynamics simulations; protein–DNA complex; zinc ions

Computational study of absorption spectra of the photoconvertible fluorescent protein EosFP in different protonation states - Imhof, Petra (Journal of Chemical Theory and Computation, 2012)
Absorption spectra of the green-to-red convertible fluorescent protein EosFP have been computed in a hybrid quantum mechanical/molecular mechanical (QM/MM) framework. The experimentally observed absorption maximum at ∼390 nm is well reproduced by the protein with a neutral chromophore, and the anionic form is computed to absorb close to the experimentally determined maximum at ∼500 nm. Absorption of a zwitterionic form is calculated to lie in the same spectral region; however, this species cannot be unambiguously assigned to the experimental spectra. Variation of the protonation states of residues surrounding the chromophore do not have significant impact on the positions of the absorption maxima. In particular, protonation of Glu212 leaves the calculated spectra largely unaffected. This is consistent with the spectra of the E212Q mutant, which differ from the wild-type spectra only in the intensities but not in the positions of the absorption bands. © 2012 American Chemical Society.
CRIS-Team Scopus Importer:2020-02-18

Editorial: Computational and Experimental Insights in Redox-Coupled Proton Pumping in Proteins - Sharma, Vivek; Imhof, Petra; Hellwig, Petra (Frontiers in Chemistry, 2021)
CRIS-Team Scopus Importer:2021-10-08
Keywords: cell respiration; mitochondria; molecular dynamics simulation; photosynthesis; proton-coupled electron donor; quantum chemical calculation; reactive oxygen species (ROS); spectroscopy

Effect of a U:G mispair on the water around DNA - Mardt, Andreas; Gorriz, Rene F.; Ferraro, Federica; Ulrich, Philip; Zahran, Mai; Imhof, Petra (Biophysical Chemistry, 2022)
DNA repair proteins are able to discriminate DNA lesions among an abundance of intact DNA with high selectivity. To investigate detectable characteristics of one specific lesion, we compare statistical results from molecular dynamics simulations of two different DNA in water, one with an intact C:G pair and one that contains a U:G mispair, and perform a comparative analysis of the water dynamics around the two. Our data show that in addition to the local DNA conformation, also the surrounding water shell exhibits significant differences that may help mispair discrimination. The chemical groups which account for a U:G mispair to exhibit a wobble conformation instead of the ‘proper’ Watson-Crick pairing of a C:G pair, that is an oxygen atom (in uracil) instead of an amino group (in cytosine), also order the water molecules around the bases such that they act predominantly as hydrogen-bond donor or acceptor to the uracil or cytosine base, respectively. These changes in water conformation stretch into the second solvation shell, which may be exploited by repair enzymes to achieve lesion detection with high efficiency.
CRIS-Team Scopus Importer:2022-03-18

Effect of the Hydration Shell on the Carbonyl Vibration in the Ala-Leu-Ala-Leu Peptide - Hassan, Irtaza; Ferraro, Federica; Imhof, Petra (Molecules, 2021)
The vibrational spectrum of the Ala-Leu-Ala-Leu peptide in solution, computed from first-principles simulations, shows a prominent band in the amide I region that is assigned to stretching of carbonyl groups. Close inspection reveals combined but slightly different contributions by the three carbonyl groups of the peptide. The shift in their exact vibrational signature is in agreement with the different probabilities of these groups to form hydrogen bonds with the solvent. The central carbonyl group has a hydrogen bond probability intermediate to the other two groups due to interchanges between different hydrogen-bonded states. Analysis of the interaction energies of individual water molecules with that group shows that shifts in its frequency are directly related to the interactions with the water molecules in the first hydration shell. The interaction strength is well correlated with the hydrogen bond distance and hydrogen bond angle, though there is no perfect match, allowing geometrical criteria for hydrogen bonds to be used as long as the sampling is sufficient to consider averages. The hydrogen bond state of a carbonyl group can therefore serve as an indicator of the solvent's effect on the vibrational frequency.
CRIS-Team WoS Importer:2021-05-14

Effects of Ring Functionalization in Anthracene-Based Cyclophanes on the Binding Properties Toward Nucleotides and DNA - Basaran, Ismet; Agafontsev, Aleksandr; Morozov, Boris; Oshchepkov, Alexander S.; Imhof, Petra; Kataev, Evgeny (Chemistry - A European Journal, 2024)
Supramolecular recognition of nucleobases and short sequences is an emerging research field focusing on possible applications to treat many diseases. Controlling the affinity and selectivity of synthetic receptors to target desired nucleotides or short sequences is a highly challenging task. Herein, we elucidate the effect of substituents in the phenyl ring of the anthracene-benzene azacyclophane on the recognition of nucleoside triphosphates (NTPs) and double-stranded DNA. We show that introducing phenyl rings increases the affinity for NTPs 10-fold and implements groove and intercalation binding modes with double-stranded DNA. NMR studies and molecular modeling calculations support the ability of cyclophanes to encapsulate nucleobases as part of nucleotides.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Cyclophanes; Fluorescence sensing; Nucleotide; Recognition; π–π interaction

Hydrogen-Bonded Network and Water Dynamics in the D-channel of Cytochrome c Oxidase - Ghane, Tahereh; Gorriz, Rene F.; Wrzalek, Sandro; Volkenandt, Senta; Dalatieh, Ferand; Reidelbach, Marco; Imhof, Petra (Journal of Membrane Biology, 2018)
Proton transfer in cytochrome c oxidase (CcO) from the cellular inside to the binuclear redox centre as well as proton pumping through the membrane takes place through proton entrance via two distinct pathways, the D- and K-channel. Both channels show a dependence of their hydration level on the protonation states of their key residues, K362 for the K-channel, and E286 or D132 for the D-channel. In the oxidative half of CcO’s catalytic cycle the D-channel is the proton-conducting path. For this channel, an interplay of protonation state of the D-channel residues with the water and hydrogen-bond dynamics has been observed in molecular dynamics simulations of the CcO protein, embedded in a lipid bi-layer, modelled in different protonation states. Protonation of residue E286 at the end of the D-channel results in a hydrogen-bonded network pointing from E286 to N139, that is against proton transport, and favouring N139 conformations which correspond to a closed asparagine gate (formed by residues N121 and N139). Consequently, the hydration level is lower than with unprotonated E286. In those models, the Asn gate is predominantly open, allowing water molecules to pass and thus increase the hydration level. The hydrogen-bonded network in these states exhibits longer life times of the Asn residues with water than other models and shows the D-channel to be traversable from the entrance, D132, to exit, E286. The D-channel can thus be regarded as auto-regulated with respect to proton transport, allowing proton passage only when required, that is the proton is located at the lower part of the D-channel (D132 to Asn gate) and not at the exit (E286).
Created from Fastlane, Scopus look-up
Keywords: Cytochrome c oxidase; Membrane protein; Proton transfer

Hydrophobic but Water-Friendly: Favorable Water-Perfluoromethyl Interactions Promote Hydration Shell Defects - Robalo, Joao R.; Streacker, Louis M.; De Oliveira, Denilson Mendes; Imhof, Petra; Ben-Amotz, Dor; Verde, Ana Vila (Journal of the American Chemical Society, 2019)
Although perfluorination is known to enhance hydrophobicity and change protein activity, its influence on hydration-shell structure and thermodynamics remains an open question. Here we address that question by combining experimental Raman multivariate curve resolution spectroscopy with theoretical classical simulations and quantum mechanical calculations. Perfluorination of the terminal methyl group of ethanol is found to enhance the disruption of its hydration-shell hydrogen bond network. Our results reveal that this disruption is not due to the associated volume change but rather to the electrostatic stabilization of the water dangling OH···F interaction. Thus, the hydration shell structure of fluorinated methyl groups results from a delicate balance of solute-water interactions that is intrinsically different from that associated with a methyl group.
CRIS-Team Scopus Importer:2020-02-18

Increasing cleavage specificity and activity of restriction endonuclease KpnI - Vasu, Kommireddy; Nagamalleswari, Easa; Zahran, Mai; Imhof, Petra; Xu, Shuang-Yong; Zhu, Zhenyu; Chan, Siu-Hong; Nagaraja, Valakunja (Nucleic Acids Research, 2013)
Restriction enzyme KpnI is a HNH superfamily endonuclease requiring divalent metal ions for DNA cleavage but not for binding. The active site of KpnI can accommodate metal ions of different atomic radii for DNA cleavage. Although Mg2+ ion higher than 500 kM mediates promiscuous activity, Ca2+ suppresses the promiscuity and induces high cleavage fidelity. Here, we report that a conservative mutation of the metal-coordinating residue D148 to Glu results in the elimination of the Ca2+-mediated cleavage but imparting high cleavage fidelity with Mg2+. High cleavage fidelity of the mutant D148E is achieved through better discrimination of the target site at the binding and cleavage steps. Biochemical experiments and molecular dynamics simulations suggest that the mutation inhibits Ca 2+-mediated cleavage activity by altering the geometry of the Ca 2+-bound HNH active site. Although the D148E mutant reduces the specific activity of the enzyme, we identified a suppressor mutation that increases the turnover rate to restore the specific activity of the high fidelity mutant to the wild-type level. Our results show that active site plasticity in coordinating different metal ions is related to KpnI promiscuous activity, and tinkering the metal ion coordination is a plausible way to reduce promiscuous activity of metalloenzymes. © The Author(s) 2013. Published by Oxford University Press.
CRIS-Team Scopus Importer:2020-02-18

In Silico Study of Camptothecin-Based Pro-Drugs Binding to Human Carboxylesterase 2 - Beierlein, Frank; Horn, Anselm; Sticht, Heinrich; Mokhir, Andriy; Imhof, Petra (Biomolecules, 2024)
Pro-drugs, which ideally release their active compound only at the site of action, i.e., in a cancer cell, are a promising approach towards an increased specificity and hence reduced side effects in chemotherapy. A popular form of pro-drugs is esters, which are activated upon their hydrolysis. Since carboxylesterases that catalyse such a hydrolysis reaction are also abundant in normal tissue, it is of great interest whether a putative pro-drug is a probable substrate of such an enzyme and hence bears the danger of being activated not just in the target environment, i.e., in cancer cells. In this work, we study the binding mode of carboxylesters of the drug molecule camptothecin, which is an inhibitor of topoisomerase I, of varying size to human carboxylesterase 2 (HCE2) by molecular docking and molecular dynamics simulations. A comparison to irinotecan, known to be a substrate of HCE2, shows that all three pro-drugs analysed in this work can bind to the HCE2 protein, but not in a pose that is well suited for subsequent hydrolysis. Our data suggest, moreover, that for the irinotecan substrate, a reactant-competent pose is stabilised once the initial proton transfer from the putative nucleophile Ser202 to the His431 of the catalytic triad has already occurred. Our simulation work also shows that it is important to go beyond the static models obtained from molecular docking and include the flexibility of enzyme–ligand complexes in solvents and at a finite temperature. Under such conditions, the pro-drugs studied in this work are unlikely to be hydrolysed by the HCE2 enzyme, indicating a low risk of undesired drug release in normal tissue.
CRIS-Team Scopus Importer:2024-03-08
Keywords: camptothecin; docking; homology model; human carboxylesterase; molecular dynamics simulations; pro-drug

Interaction of thymine dna glycosylase with oxidised 5-methyl-cytosines in their amino-and imino-forms - Volkenandt, Senta; Beierlein, Frank; Imhof, Petra (Molecules, 2021)
Thymine DNA Glycosylase (TDG) is an enzyme of the base excision repair mechanism and removes damaged or mispaired bases from DNA via hydrolysis of the glycosidic bond. Specificity is of high importance for such a glycosylase, so as to avoid the damage of intact DNA. Among the substrates reported for TDG are mispaired uracil and thymine but also formyl-cytosine and carboxyl-cytosine. Methyl-cytosine and hydroxylmethyl-cytosine are, in contrast, not processed by the TDG enzyme. We have in this work employed molecular dynamics simulations to explore the conformational dynamics of DNA carrying a formyl-cytosine or carboxyl-cytosine and compared those to DNA with the non-cognate bases methyl-cytosine and hydroxylmethyl-cytosine, as amino and imino tautomers. Whereas for the mispairs a wobble conformation is likely decisive for recogni-tion, all amino tautomers of formyl-cytosine and carboxyl-cytosine exhibit the same Watson–Crick conformation, but all imino tautomers indeed form wobble pairs. The conformational dynamics of the amino tautomers in free DNA do not exhibit differences that could be exploited for recogni-tion, and also complexation to the TDG enzyme does not induce any alteration that would indicate preferable binding to one or the other oxidised methyl-cytosine. The imino tautomers, in contrast, undergo a shift in the equilibrium between a closed and a more open, partially flipped state, towards the more open form upon complexation to the TDG enzyme. This stabilisation of the more open conformation is most pronounced for the non-cognate bases methyl-cytosine and hydroxyl-cytosine and is thus not a likely mode for recognition. Moreover, calculated binding affinities for the different forms indicate the imino forms to be less likely in the complexed DNA. These findings, together with the low probability of imino tautomers in free DNA and the indifference of the complexed amino tautomers, suggest that discrimination of the oxidised methyl-cytosines does not take place in the initial complex formation.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Alchemical free energy calculations; Amino imino tautomers; Molecular dynamics simulations; Oxidised methyl-cytosine; Thymine DNA glycosylase

Interactions of the DNA Repair Enzyme Human Thymine DNA Glycosylase with Cognate and Noncognate DNA - Kanaan, Natalia; Imhof, Petra (Biochemistry, 2018)
Glycosylases specifically recognize and flip their target base out of the DNA helix into the enzyme's active site. Our simulations show that a partially flipped state, already present in free DNA carrying a T:G mispair, becomes the more probable state compared to the closed state after binding of thymine DNA glycosylase (TDG). Paired thymine (T:A) or methyl-cytosine (mC:G) does not exhibit a partially flipped state in free or complexed DNA. Important enzyme-DNA interactions exhibit significant strength in the intrahelical and extrahelical TDG-DNA complexes. The computed binding free energy differences suggest these interactions account for the stabilization of the partially flipped state, thereby driving the T:G mispair toward base flip. In the fully flipped state, the cognate base thymine is significantly better accommodated in the enzyme's active site than noncognate bases are, suggesting the hydrolysis step as the last of several stages at which base recognition can be achieved.
Created from Fastlane, Scopus look-up

Interplay of Hydration and Protonation Dynamics in the K-Channel of Cytochrome c Oxidase - Gorriz, Rene F.; Imhof, Petra (Biomolecules, 2022)
Cytochrome c oxidase is a membrane protein of the respiratory chain that consumes protons and molecular oxygen to produce water and uses the resulting energy to pump protons across the membrane. Our molecular dynamics simulations with an excess proton located at different positions in one of the proton-conducting channels, the K-channel, show a clear dependence of the number of water molecules inside the channel on the proton position. A higher hydration level facilitates the formation of hydrogen-bonded chains along which proton transfer can occur. However, a sufficiently high hydration level for such proton transport is observed only when the excess proton is located above S365, i.e., the lower third of the channel. From the channel entrance up to this point, proton transport is via water molecules as proton carriers. These hydronium ions move with their surrounding water molecules, up to K362, filling and widening the channel. The conformation of K362 depends on its own protonation state and on the hydration level, suggesting its role to be proton transport from a hydronium ion at the height of K362 to the upper part of the channel via a conformational change. The protonation-dependent conformational dynamics of E101 at the bottom of the channel renders proton transfer via E101 unlikely. Instead, its role is rather that of an amplifier of H96’s proton affinity, suggesting H96 as the initial proton acceptor.
CRIS-Team Scopus Importer:2022-11-25
Keywords: cytochrome c oxidase; hydration level; molecular dynamics simulations; proton transfer

Long-range allostery mediates cooperative adenine nucleotide binding by the Ski2-like RNA helicase Brr2 - Absmeier, Eva; Vester, Karen; Ghane, Tahereh; Burakovskiy, Dmitry; Milon, Pohl; Imhof, Petra; Rodnina, Marina; Santos, Karine F.; Wahl, Markus C. (Journal of Biological Chemistry, 2021)
Brr2 is an essential Ski2-like RNA helicase that exhibits a unique structure among the spliceosomal helicases. Brr2 harbors a catalytically active N-terminal helicase cassette and a structurally similar but enzymatically inactive C-terminal helicase cassette connected by a linker region. Both cassettes contain a nucleotide-binding pocket, but it is unclear whether nucleotide binding in these two pockets is related. Here we use biophysical and computational methods to delineate the functional connectivity between the cassettes and determine whether occupancy of one nucleotide-binding site may influence nucleotide binding at the other cassette. Our results show that Brr2 exhibits high specificity for adenine nucleotides, with both cassettes binding ADP tighter than ATP. Adenine nucleotide affinity for the inactive C-terminal cassette is more than two orders of magnitude higher than that of the active N-terminal cassette, as determined by slow nucleotide release. Mutations at the intercassette surfaces and in the connecting linker diminish the affinity of adenine nucleotides for both cassettes. Moreover, we found that abrogation of nucleotide binding at the C-terminal cassette reduces nucleotide binding at the N-terminal cassette 70 A away. Molecular dynamics simulations identified structural communication lines that likely mediate these long-range allosteric effects, predominantly across the intercassette interface. Together, our results reveal intricate networks of intramolecular interactions in the complex Brr2 RNA helicase, which fine-tune its nucleotide affinities and which could be exploited to regulate enzymatic activity during splicing.
CRIS-Team WoS Importer:2021-08-06

Magnesium-dependent active-site conformational selection in the Diels-Alderase ribozyme - Berezniak, Tomasz; Zahran, Mai; Imhof, Petra; Jaeschke, Andres; Smith, Jeremy C. (Journal of the American Chemical Society, 2010)
The Diels-Alderase ribozyme, an in vitro-evolved ribonucleic acid enzyme, accelerates the formation of carbon-carbon bonds between an anthracene diene and a maleimide dienophile in a [4 + 2] cycloaddition, a reaction with broad application in organic chemistry. Here, the Diels-Alderase ribozyme is examined via molecular dynamics (MD) simulations in both crystalline and aqueous solution environments. The simulations indicate that the catalytic pocket is highly dynamic. At low Mg2+ ion concentrations, inactive states with the catalytic pocket closed dominate. Stabilization of the enzymatically active, open state of the catalytic pocket requires a high concentration of Mg 2+ ions (e.g., 54 mM), with cations binding to specific phosphate sites on the backbone of the residues bridging the opposite strands of the pocket. The free energy profile for pocket opening at high Mg2+ cation concentration exhibits a double minimum, with a barrier to opening of ∼5.5 kJ/mol and the closed state ∼3 kJ/mol lower than the open state. Selection of the open state on substrate binding leads to the catalytic activity of the ribozyme. The simulation results explain structurally the experimental observation that full catalytic activity depends on the Mg2+ ion concentration. © 2010 American Chemical Society.
CRIS-Team Scopus Importer:2020-02-18

Mechanism of DNA recognition by the restriction enzyme EcoRV - Zahran, Mai; Daidone, Isabella; Smith, Jeremy C.; Imhof, Petra (Journal of Molecular Biology, 2010)
EcoRV, a restriction enzyme in Escherichia coli, destroys invading foreign DNA by cleaving it at the center step of a GATATC sequence. In the EcoRV-cognate DNA crystallographic complex, a sharp kink of 50° has been found at the center base-pair step (TA). Here, we examine the interplay between the intrinsic propensity of the cognate sequence to kink and the induction by the enzyme by performing all-atom molecular dynamics simulations of EcoRV unbound and interacting with three DNA sequences: the cognate sequence, GATATC (TA); the non-cognate sequence, GAATTC (AT); and with the cognate sequence methylated on the first adenine GACH3TATC (TA-CH3). In the unbound EcoRV, the cleft between the two C-terminal subdomains is found to be open. Binding to AT narrows the cleft and forms a partially bound state. However, the intrinsic bending propensity of AT is insufficient to allow tight binding. In contrast, the cognate TA sequence is easier to bend, allowing specific, high-occupancy hydrogen bonds to form in the complex. The absence of cleavage for this methylated sequence is found to arise from the loss of specific hydrogen bonds between the first adenine of the recognition sequence and Asn185. On the basis of the results, we suggest a three-step recognition mechanism. In the first step, EcoRV, in an open conformation, binds to the DNA at a random sequence and slides along it. In the second step, when the two outer base pairs, GAxxTC, are recognized, the R loops of the protein become more ordered, forming strong hydrogen-bonding interactions, resulting in a partially bound EcoRV-DNA complex. In the third step, the flexibility of the center base pair is probed, and in the case of the full cognate sequence the DNA bends, the complex strengthens and the protein and DNA interact more closely, allowing cleavage. © 2010 Elsevier Ltd.
CRIS-Team Scopus Importer:2020-02-18
Keywords: Direct/indirect readout; EcoRV; Protein-DNA interaction; Sequence recognition

Mechanism of the Glycosidic Bond Cleavage of Mismatched Thymine in Human Thymine DNA Glycosylase Revealed by Classical Molecular Dynamics and Quantum Mechanical/Molecular Mechanical Calculations - Kanaan, Natalia; Crehuet, Ramon; Imhof, Petra (Journal of Physical Chemistry B, 2015)
Base excision of mismatched or damaged nucleotides catalyzed by glycosylase enzymes is the first step of the base excision repair system, a machinery preserving the integrity of DNA. Thymine DNA glycosylase recognizes and removes mismatched thymine by cleaving the C1′-N1 bond between the base and the sugar ring. Our quantum mechanical/molecular mechanical calculations of this reaction in human thymine DNA glycosylase reveal a requirement for a positive charge in the active site to facilitate C1′-N1 bond scission: protonation of His151 significantly lowers the free energy barrier for C1′-N1 bond dissociation compared to the situation with neutral His151. Shuttling a proton from His151 to the thymine base further reduces the activation free energy for glycosidic bond cleavage. Classical molecular dynamics simulations of the H151A mutant suggest that the mutation to the smaller, neutral, residue increases the water accessibility of the thymine base, rendering direct proton transfer from the bulk feasible. Quantum mechanical/molecular mechanical calculations of the glycosidic bond cleavage reaction in the H151A mutant show that the activation free energy is slightly lower than in the wild-type enzyme, explaining the experimentally observed higher reaction rates in this mutant.
CRIS-Team Scopus Importer:2020-02-18

Mode of Metal Ligation Governs Inhibition of Carboxypeptidase A - Amador Balderas, Jorge Antonio; Beierlein, Frank; Horn, Anselm; Volkenandt, Senta; Völcker, Leon; Mokhtari, Nikoo; Epee Ndongue, Jules Cesar; Imhof, Petra (International Journal of Molecular Sciences, 2024)
Carboxypeptidase is a Zn-dependent protease that specifically recognises and hydrolyses peptides with a hydrophobic side chain at the C-terminal residue. According to hydrolysis mechanisms proposed in the literature, catalysis requires a water molecule to be close to the Zn ion so as to be activated as a nucleophile. Among small molecules that resemble the slowly hydrolysed Gly-Tyr peptide, which have been previously designed as inhibitors and characterised structurally, a variant with the terminal amino acid in a D-configuration has been the most effective. Our molecular dynamics simulations of carboxypeptidase complexed with different variants of those inhibitor ligands as well as variants of the Gly-Tyr peptide show that the strength of the inhibitory effect is not related to the binding strength of the ligand. Our data rather support an earlier notion that the inhibition is, at least partially, due to blocking a coordination site at the Zn ion by the ligand coordinating the metal ion in a bidentate fashion.<br
Keywords: carboxypeptidase A; peptide hydrolysis; zinc coordination; inhibition; molecular dynamics simulations

Modulation of a ligand's energy landscape and kinetics by the chemical environment - Held, Martin; Imhof, Petra; Keller, Bettina G.; Noe, Frank (Journal of Physical Chemistry B, 2012)
Understanding how the chemical environment modulates the predominant conformations and kinetics of flexible molecules is a core interest of biochemistry and a prerequisite for the rational design of synthetic catalysts. This study combines molecular dynamics simulation and Markov state models (MSMs) to a systematic computational strategy for investigating the effect of the chemical environment of a molecule on its conformations and kinetics. MSMs allow quantities to be computed that are otherwise difficult to access, such as the metastable sets, their free energies, and the relaxation time scales related to the rare transitions between metastable states. Additionally, MSMs are useful to identify observables that may act as sensors for the conformational or binding state of the molecule, thus guiding the design of experiments. In the present study, the conformation dynamics of UDP-GlcNAc are studied in vacuum, water, water + Mg2+, and in the protein UDP-GlcNAc 2-epimerase. It is found that addition of Mg2+ significantly affects the conformational stability, thermodynamics, and kinetics of UDP-GlcNAc. In particular, the slowest structural process, puckering of the GlcNAc sugar, depends on the overall conformation of UDP-GlcNAc and may thus act as a sensor of whether Mg2+ is bound or not. Interestingly, transferring the molecule from vacuum to water makes the protein-binding conformations UDP-GlcNAc first accessible, while adding Mg2+ further stabilizes them by specifically associating to binding-competent conformations. While Mg2+ is not cocrystallized in the UDP-GlcNAc 2-epimerase complex, the selectively stabilized Mg2+/UDP-GlcNAc complex may be a template for the bound state, and Mg2+ may accompany the binding-competent ligand conformation to the binding pocket. This serves as a possible explanation of the enhanced epimerization rate in the presence of Mg2+. This role of Mg 2+ has previously not been described and opens the question whether "binding co-factors" may be a concept of general relevance for protein-ligand binding. © 2012 American Chemical Society.
CRIS-Team Scopus Importer:2020-02-18

Molecular Dynamics Simulations of a Chimeric Androgen Receptor Protein (SPARKI) Confirm the Importance of the Dimerization Domain on DNA Binding Specificity - Helabad, Mahdi Bagherpoor; Volkenandt, Senta; Imhof, Petra (Frontiers in Bioscience, 2020)
The DNA binding domains of Androgen/Glucocorticoid receptors (AR/GR), members of class I steroid receptors, bind as a homo-dimer to a cis-regulatory element. These response elements are arranged as inverted repeat (IR) of hexamer "AGAACA", separated with a 3 base pairs spacer. DNA binding domains of the Androgen receptor, AR-DBDs, in addition, selectively recognize a direct-like repeat (DR) arrangement of this hexamer. A chimeric AR protein, termed SPARKI, in which the second zinc-binding motif of AR is swapped with that of GR, however, fails to recognize DR-like elements. By molecular dynamic simulations, we identify how the DNA binding domains of the wild type AR/GR, and also the chimeric SPARKI model, distinctly interact with both IR and DR response elements. AR binds more strongly to DR than GR binds to IR elements. A SPARKI model built from the structure of the AR (SPARKI-AR) shows significantly fewer hydrogen bond interactions in complex with a DR sequence than with an IR sequence. Moreover, a SPARKI model based on the structure of the GR (SPARKI-GR) shows a considerable distortion in its dimerization domain when complexed to a DR-DNA whereas it remains in a stable conformation in a complex with an IR-DNA. The diminished interaction of SPARKI-AR with and the instability of SPARKI-GR on DR response elements agree with SPARKI's lack of affinity for these sequences. The more GR-like binding specificity of the chimeric SPARKI protein is further emphasized by both SPARKI models binding even more strongly to IR elements than observed for the DNA binding domain of the GR.
Keywords: androgen receptor; glucocorticoid receptor; response element; protein-DNA interaction; chimeric SPARKI protein

New fluorogenic triacylglycerols as sensors for dynamic measurement of lipid oxidation - Handke, Maria; Beierlein, Frank; Imhof, Petra; Schiedel, Matthias; Hammann, Simon (Analytical and Bioanalytical Chemistry, 2024)
Lipids are major constituents of food but are also highly relevant substructures of drugs and are increasingly applied for the development of lipid-based drug delivery systems. Lipids are prone to oxidative degradation, thus affecting the quality of food or medicines. Therefore, analytical methods or tools that enable the degree of lipid oxidation to be assessed are of utmost importance to guarantee food and drug safety. Herein, we report the design, synthesis and application of the first-in-class fluorogenic triacylglycerols that enable dynamic monitoring of lipid oxidation via straightforward fluorescence readout. Our fluorogenic triacylglycerols can be used in both aqueous and lipid-based environments. Furthermore, we showed that the sensitivity of our fluorescent tracers towards oxidation could be tuned by incorporating either saturated or unsaturated acyl chains in their triacylglycerol core structure. With this, we provide a first proof of principle for the applicability of fluorescently labelled triacylglycerols as tracers to monitor the dynamics of lipid oxidation, thus paving the way for novel discoveries in the area of lipid analytics. Graphical Abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-11-29
Keywords: Assay; Click chemistry; Fluorogenic substrate; Lipid oxidation; Triacylglycerol

Oxidation Enhances Binding of Extrahelical 5-Methyl-Cytosines by Thymine DNA Glycosylase - Beierlein, Frank; Volkenandt, Senta; Imhof, Petra (Journal of Physical Chemistry B, 2022)
The DNA repair protein thymine DNA glycosylase (TDG) removes mispaired or damaged bases, such as oxidized methyl-cytosine, from DNA by cleavage of the glycosidic bond between the sugar and the target base flipped into the enzyme’s active site. The enzyme is active against formyl-cytosine and carboxyl-cytosine, whereas the lower oxidized hydroxymethyl-cytosine and methyl-cytosine itself are not processed by the enzyme. Molecular dynamics simulations with thermodynamic integration of TDG complexed to DNA carrying one of four different (oxidized) methyl-cytosine bases in extrahelcial conformation, methyl-cytosine (mC), hydroxymethyl-cytosine (hmC), formyl-cytosine (fC), or carboxyl-cytosine (caC), show a more favorable binding affinity of the higher oxidized forms, fC and caC, than the nonsubstrate bases hmC and mC. Despite rather comparable, reaction-competent conformations of the flipped bases in the active site of the enzyme, more and stronger interactions with active site residues account for the preferred binding of the higher oxidized bases. Binding of the negatively charged caC and the neutral fC are strengthened by interactions with positively charged His151. Our calculated proton affinities find this protonation state of His151 the preferred one in the presence of caC and conceivable in the presence of fC as well as increasing the binding affinity toward the two bases. Discrimination of the substrate bases is further achieved by the backbone of Tyr152 that forms a strong hydrogen bond to the carboxyl and formyl oxygen atoms of caC and fC, respectively, a contact that is completely lacking in mC and much weaker in hmC. Overall, our computational results indicate that the enzyme discriminates the different oxidation forms of methyl-cytosine already at the formation of the extrahelical complexes.<br

Phosphodiester hydrolysis computed for cluster models of enzymatic active sites - Batebi, Hossein; Imhof, Petra (Theoretical Chemistry Accounts, 2016)
Computation of phosphodiester hydrolysis in different models with one or two metal ions, representing typical active site architectures of nucleases, reveals an associative mechanism to be favorable in all of the cases studied in this work. Direct attack of the nucleophilic water molecule with proton transfer to the phosphate group is facilitated by an extra positive charge as provided by a metal ion located at the attack site or a positively charged histidine residue, whereas no such contribution can be observed on leaving group departure. A major catalytic effect is found by proton transfer from the nucleophilic water molecule to a histidine–aspartate cluster. Attack of the thus generated hydroxide ion on the phosphate group is just sufficiently stabilized by the metal ions to allow subsequent P–O bond dissociation.
CRIS-Team Scopus Importer:2020-02-18
Keywords: Metal-ion catalysis; Nucleophile activation; Phosphate hydrolysis

Prediction of perturbed proton transfer networks - Reidelbach, Marco; Weber, Marcus; Imhof, Petra (PLoS ONE, 2018)
The transfer of protons through proton translocating channels is a complex process, for which direct samplings of different protonation states and side chain conformations in a transition network calculation provide an efficient, bias-free description. In principle, a new transition network calculation is required for every unsampled change in the system of interest, e.g. an unsampled protonation state change, which is associated with significant computational costs. Transition networks void of or including an unsampled change are termed unperturbed or perturbed, respectively. Here, we present a prediction method, which is based on an extensive coarse-graining of the underlying transition networks to speed up the calculations. It uses the minimum spanning tree and a corresponding sensitivity analysis of an unperturbed transition network as initial guess and refinement parameter for the determination of an unknown, perturbed transition network. Thereby, the minimum spanning tree defines a sub-network connecting all nodes without cycles and minimal edge weight sum, while the sensitivity analysis analyzes the stability of the minimum spanning tree towards individual edge weight reductions. Using the prediction method, we are able to reduce the calculation costs in a model system by up to 80%, while important network properties are maintained in most predictions.
CRIS-Team Scopus Importer:2020-02-18

Protonation dynamics in the K-channel of cytochrome C oxidase estimated from molecular dynamics simulations - Stegmaier, Vincent; Gorriz, Rene F.; Imhof, Petra (Processes, 2021)
Proton transfer reactions are one of the most fundamental processes in biochemistry. We present a simplistic approach for estimating proton transfer probabilities in a membrane protein, cytochrome c oxidase. We combine short molecular dynamics simulations at discrete protonation states with a Monte Carlo approach to exchange between those states. Requesting for a proton transfer the existence of a hydrogen-bonded connection between the two source and target residues of the exchange,restricts the acceptance of transfers to only those in which a proton-relay is possible. Together with an analysis of the hydrogen-bonded connectivity in one of the proton-conducting channels of cytochrome c oxidase, this approach gives insight into the protonation dynamics of the hydrogen-bonded networks. The connectivity and directionality of the networks are coupled to the conformation of an important protein residue in the channel, K362, rendering proton transfer in the entire channel feasible in only one of the two major conformations. Proton transport in the channel can thus be regulated by K362 not only through its possible role as a proton carrier itself, but also by allowing or preventing proton transport via water residues.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Hydrogen-bonded network; Proton transfer; Replica exchange; Sampling

Protonation-State Dependence of Hydration and Interactions in the Two Proton-Conducting Channels of Cytochrome c Oxidase - Gorriz, Rene F.; Volkenandt, Senta; Imhof, Petra (International Journal of Molecular Sciences, 2023)
Cytochrome c Oxidase (CcO), a membrane protein of the respiratory chain, pumps protons against an electrochemical gradient by using the energy of oxygen reduction to water. The (“chemical”) protons required for this reaction and those pumped are taken up via two distinct channels, named D-channel and K-channel, in a step-wise and highly regulated fashion. In the reductive phase of the catalytic cycle, both channels transport protons so that the pumped proton passes the D-channel before the “chemical” proton has crossed the K-channel. By performing molecular dynamics simulations of CcO in the O→E redox state (after the arrival of the first reducing electron) with various combinations of protonation states of the D- and K-channels, we analysed the effect of protonation on the two channels. In agreement with previous work, the amount of water observed in the D-channel was significantly higher when the terminal residue E286 was not (yet) protonated than when the proton arrived at this end of the D-channel and E286 was neutral. Since a sufficient number of water molecules in the channel is necessary for proton transport, this can be understood as E286 facilitating its own protonation. K-channel hydration shows an even higher dependence on the location of the excess proton in the K-channel. Also in agreement with previous work, the K-channel exhibits a very low hydration level that likely hinders proton transfer when the excess proton is located in the lower part of the K-channel, that is, on the N-side of S365. Once the proton has passed S365 (towards the reaction site, the bi-nuclear centre (BNC)), the amount of water in the K-channel provides hydrogen-bond connectivity that renders proton transfer up to Y288 at the BNC feasible. No significant direct effect of the protonation state of one channel on the hydration level, hydrogen-bond connectivity, or interactions between protein residues in the other channel could be observed, rendering proton conductivity in the two channels independent of each other. Regulation of the order of proton uptake and proton passage in the two channels such that the “chemical” proton leaves its channel last must, therefore, be achieved by other means of communication, such as the location of the reducing electron.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Cytochrome c Oxidase; molecular dynamics simulations; protonation and hydration

Protonation-State-Dependent Communication in Cytochrome c Oxidase - Helabad, Mandi Bagherpoor; Ghane, Tahereh; Reidelbach, Marco; Woelke, Anna Lena; Knapp, Ernst Walter; Imhof, Petra (Biophysical Journal, 2017)
Proton transfer in cytochrome c oxidase from the cellular inside to the binuclear redox center (BNC) can occur through two distinct pathways, the D- and K-channels. For the protein to function as both a redox enzyme and a proton pump, proton transfer into the protein toward the BNC or toward a proton loading site (and ultimately through the membrane) must be highly regulated. The PR → F transition is the first step in a catalytic cycle that requires proton transfer from the bulk at the N-side to the BNC. Molecular dynamics simulations of the PR → F intermediate of this transition, with 16 different combinations of protonation states of key residues in the D- and K-channel, show the impact of the K-channel on the D-channel to be protonation-state dependent. Strength as well as means of communication, correlations in positions, or communication along the hydrogen-bonded network depends on the protonation state of the K-channel residue K362. The conformational and hydrogen-bond dynamics of the D-channel residue N139 is regulated by an interplay of protonation in the D-channel and K362. N139 thus assumes a gating function by which proton passage through the D-channel toward E286 is likely facilitated for states with protonated K362 and unprotonated E286. In contrast, proton passage through the D-channel is hindered by N139's preference for a closed conformation in situations with protonated E286.
CRIS-Team Scopus Importer:2020-02-18

Proton transfer in the D-channel of cytochrome c oxidase modeled by a transition network approach - Reidelbach, Marco; Imhof, Petra (Biochimica Et Biophysica Acta-General Subjects, 2020)
Background: Determination of proton uptake pathways in Cytochrome c Oxidase is difficult due to the complexity of the system. The transition networks approach allows sampling of proton transfer pathways without predefined reaction coordinate. Methods: Computation of the proton transfer pathways in a model of the D-channel of cytochrome c oxidase has been performed by a transition network approach that combines discrete, optimisation based and molecular dynamics based sampling. Results: The optimal pathway involves an opening of the so-called asparagine gate, hydration of the asparagine region, the formation of a hydrogen-bonded chain, and finally concerted proton hole transport along this chain. The optimal pathway finds the protonation of residue H26 close to the channel entrance favourable for lowering the transition energies of subsequent steps, in particular, opening of the Asn gate and formation of a hydrogen-bonded chain. Residue Y33 plays an important role in shuttling the transferred proton hole. Conclusions: The optimal pathway found by the transition network approach shows the same important characteristics as pathways determined earlier by other methods. The computed barrier and reaction energies are also in good agreement with previous studies. The transition network approach provides an alternative to explore pathways in complex systems. General significance: The correct function of the enzyme as oxidase and proton pump depends on the interplay of several redox and proton transport steps. Understanding the proton transport mechanism is therefore key to understanding the protein's function. The complex nature of long- distances proton transfer through a protein requires a non-trivial simulation strategy.
Created from Fastlane, Scopus look-up
Keywords: Cytochrome c oxidase; Proton transfer; Reaction path sampling; Transition networks

Proton transfer pathways, energy landscape, and kinetics in creatine-water systems - Ivchenko, Olga; Whittleston, Chris S.; Carr, Joanne M.; Imhof, Petra; Goerke, Steffen; Bachert, Peter; Wales, David J. (Journal of Physical Chemistry B, 2014)
We study the exchange processes of the metabolite creatine, which is present in both tumorous and normal tissues and has NH2 and NH groups that can transfer protons to water. Creatine produces chemical exchange saturation transfer (CEST) contrast in magnetic resonance imaging (MRI). The proton transfer pathway from zwitterionic creatine to water is examined using a kinetic transition network constructed from the discrete path sampling approach and an approximate quantum-chemical energy function, employing the self-consistent-charge density-functional tight-binding (SCC-DFTB) method. The resulting potential energy surface is visualized by constructing disconnectivity graphs. The energy landscape consists of two distinct regions corresponding to the zwitterionic creatine structures and deprotonated creatine. The activation energy that characterizes the proton transfer from the creatine NH2 group to water was determined from an Arrhenius fit of rate constants as a function of temperature, obtained from harmonic transition state theory. The result is in reasonable agreement with values obtained in water exchange spectroscopy (WEX) experiments. © 2014 American Chemical Society.
CRIS-Team Scopus Importer:2020-02-18

Proton transfer pathways in an aspartate-water cluster sampled by a network of discrete states - Reidelbach, Marco; Betz, Fridtjof; Maeusle, Raquel Maya; Imhof, Petra (Chemical Physics Letters, 2016)
Proton transfer reactions are complex transitions due to the size and flexibility of the hydrogen-bonded networks along which the protons may “hop”. The combination of molecular dynamics based sampling of water positions and orientations with direct sampling of proton positions is an efficient way to capture the interplay of these degrees of freedom in a transition network. The energetically most favourable pathway in the proton transfer network computed for an aspartate-water cluster shows the pre-orientation of water molecules and aspartate side chains to be a pre-requisite for the subsequent concerted proton transfer to the product state.
CRIS-Team Scopus Importer:2020-02-18
Keywords: Discretisation; Proton transfer; Reaction pathways; Sampling; Transition network

Quantifying how step-wise fluorination tunes local solute hydrophobicity, hydration shell thermodynamics and the quantum mechanical contributions of solute-water interactions - Robalo, Joao R.; Mendes De Oliveira, Denilson; Imhof, Petra; Ben-Amotz, Dor; Vila Verde, Ana (Physical Chemistry Chemical Physics, 2020)
The ability to locally tune solute-water interactions and thus control the hydrophilic/hydrophobic character of a solute is key to control molecular self-assembly and to develop new drugs and biocatalysts; it has been a holy grail in synthetic chemistry and biology. To date, the connection between (i) the hydrophobicity of a functional group; (ii) the local structure and thermodynamics of its hydration shell; and (iii) the relative influence of van der Waals (dispersion) and electrostatic interactions on hydration remains unclear. We investigate this connection using spectroscopic, classical simulation and ab initio methods by following the transition from hydrophile to hydrophobe induced by the step-wise fluorination of methyl groups. Along the transition, we find that water-solute hydrogen bonds are progressively transformed into dangling hydroxy groups. Each structure has a distinct thermodynamic, spectroscopic and quantum-mechanical signature connected to the associated local solute hydrophobicity and correlating with the relative contribution of electrostatics and dispersion to the solute-water interactions.
CRIS-Team WoS Importer:2020-11-06

Quantum mechanical/molecular mechanical analysis of the catalytic mechanism of phosphoserine phosphatase - Krachtus, Dieter; Smith, Jeremy C.; Imhof, Petra (Molecules, 2018)
Phosphoserine phosphatase (PSP), a member of the haloacid dehalogenase (HAD) superfamily that comprises the vast majority of phosphotransferases, is likely a steady-state regulator of the level of D-serine in the brain. The proposed catalytic cycle of PSP consists of a two-step mechanism: formation of a phospho-enzyme intermediate by phosphate transfer to Asp11 and its subsequent hydrolysis. Our combined quantum mechanical/molecular mechanical (QM/MM) calculations of the reaction pathways favour a dissociative mechanism of nucleophilic substitution via a trigonal-planar metaphosphate-like configuration for both steps, associated with proton transfer to the leaving group or from the nucleophile. This proton transfer is facilitated by active site residue Asp13 that acts as both a general base and a general acid. Free energy calculation on the reaction pathways further support the structural role of the enzymatic environment and the active site architecture. The choice of a proper reaction coordinate along which to bias the free energy calculations can be guided by a projection of the canonical reaction coordinate obtained from a chain-of-state optimisation onto important internal coordinates.
CRIS-Team Scopus Importer:2020-02-18
Keywords: Phosphoserine phosphatase; QM/MM; Reaction pathways; reaction coordinate

Retraction Notice to: Protonation State-Dependent Communication in Cytochrome c Oxidase - Helabad, Mandi Bagherpoor; Ghane, Tahereh; Reidelbach, Marco; Woelke, Anna Lena; Knapp, Ernst-Walter; Imhof, Petra (Biophysical Journal, 2017)
CRIS-Team Scopus Importer:2020-02-18

Role of AP-endonuclease (Ape1) active site residues in stabilization of the reactant enzyme-DNA complex - Batebi, Hossein; Dragelj, Jovan; Imhof, Petra (Proteins-Structure Function and Bioinformatics, 2018)
Apurinic/apyrimidinic endonuclease 1 (Ape1) is an important metal-dependent enzyme in the base excision repair mechanism, responsible for the backbone cleavage of abasic DNA through a phosphate hydrolysis reaction. Molecular dynamics simulations of Ape1 complexed to its substrate DNA performed for models containing 1 or 2 Mg2+-ions as cofactor located at different positions show a complex with 1 metal ion bound on the leaving group site of the scissile phosphate to be the most likely reaction-competent conformation. Active-site residue His309 is found to be protonated based on pKa calculations and the higher conformational stability of the Ape1-DNA substrate complex compared to scenarios with neutral His309. Simulations of the D210N mutant further support the prevalence of protonated His309 and strongly suggest Asp210 as the general base for proton acceptance by a nucleophilic water molecule.
Created from Fastlane, Scopus look-up
Keywords: abasic site; DNA repair; endonuclease; metal-ions; molecular dynamics; pKa values; protein-DNA complex

Role of magnesium ions in DNA recognition by the EcoRV restriction endonuclease - Zahran, Mai; Berezniak, Tomasz; Imhof, Petra; Smith, Jeremy C. (FEBS letters, 2011)
The restriction endonuclease EcoRV binds two magnesium ions. One of these ions, MgA2+, binds to the phosphate group where the cleavage occurs and is required for catalysis, but the role of the other ion, MgB2+ is debated. Here, multiple independent molecular dynamics simulations suggest that MgB2+ is crucial for achieving a tightly bound protein-DNA complex and stabilizing a conformation that allows cleavage. In the absence of MgB2+ in all simulations the protein-DNA hydrogen bond network is significantly disrupted and the sharp kink at the central base pair step of the DNA, which is observed in the two-metal complex, is not present. Also, the active site residues rearrange in such a way that the formation of a nucleophile, required for DNA hydrolysis, is unlikely. © 2011 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2020-02-18
Keywords: Divalent metal ions; Mg; Nuclease; Protein-DNA interaction; Restriction enzyme

Sequences flanking the core-binding site modulate glucocorticoid receptor structure and activity - Schoene, Stefanie; Jurk, Marcel; Helabad, Mahdi Bagherpoor; Dror, Iris; Lebars, Isabelle; Kieffer, Bruno; Imhof, Petra; Rohs, Remo; Vingron, Martin; Thomas-Chollier, Morgane; Meijsing, Sebastiaan H. (Nature Communications, 2016)
The glucocorticoid receptor (GR) binds as a homodimer to genomic response elements, which have particular sequence and shape characteristics. Here we show that the nucleotides directly flanking the core-binding site, differ depending on the strength of GR-dependent activation of nearby genes. Our study indicates that these flanking nucleotides change the three-dimensional structure of the DNA-binding site, the DNA-binding domain of GR and the quaternary structure of the dimeric complex. Functional studies in a defined genomic context show that sequence-induced changes in GR activity cannot be explained by differences in GR occupancy. Rather, mutating the dimerization interface mitigates DNA-induced changes in both activity and structure, arguing for a role of DNA-induced structural changes in modulating GR activity. Together, our study shows that DNA sequence identity of genomic binding sites modulates GR activity downstream of binding, which may play a role in achieving regulatory specificity towards individual target genes.
CRIS-Team Scopus Importer:2020-02-18

Stereoselection in the diels-alderase ribozyme: A molecular dynamics study - Berezniak, Tomasz; Jaeschke, Andres; Smith, Jeremy C.; Imhof, Petra (Journal of Computational Chemistry, 2012)
The Diels-Alderase ribozyme is an in vitro-evolved ribonucleic acid enzyme that catalyzes a [4 + 2] cycloaddition reaction between an anthracene diene and a maleimide dienophile. The ribozyme can in principle be used to selectively synthesize only one product enantiomer, depending on which of the two entrances to the catalytic pocket, "front" or "back", the substrate is permitted to use. Here, we investigate stereoselection and substrate recognition in the ribozyme by means of multiple molecular dynamics simulations, performed on each of the two substrates individually in the pocket, on the reactant state, and on the product state. The results are consistent with a binding mechanism in which the maleimide likely binds first followed by the anthracene, which enters preferentially through the front door. The free energy profiles for anthracene binding indicate that the pre-(R,R)-enantiomer conformation is slightly preferred, in agreement with the experimentally observed small enantiomeric excess of the (R,R)-enantiomer of the product. The reactant state is stabilized by the simultaneous presence of both substrates bound to their binding sites in the hydrophobic pocket as well as by stacking interactions between them. © 2012 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2020-02-18
Keywords: binding mechanism; enzyme catalysis; molecular dynamics; RNA; stereoselection

Structural analysis of DNA molecule in a confined shell - Maity, Arghya; Mathur, Neha; Imhof, Petra; Singh, Navin (Physica A-Statistical Mechanics and Its Applications, 2023)
Recent advances in operating and manipulating DNA have provided unique experimental possibilities in many fields of DNA research, especially in gene therapy. Researchers have deployed many techniques, experimental and theoretical, to study the DNA structure changes due to external perturbation. It is crucial to understand the structural and dy-namical changes in the DNA molecules in a confined state to understand and control the self-assembly of DNA confined in a chamber or nano-channel for various applications. In the current manuscript, we extend the work study the effect of confinement on the thermal stability and the structural properties of duplex DNA. The present work is an extension of our previous research works (Maity et al., 2019; 2020). For our study we have considered a 1 BNA chain that is confined in a cylindrical geometry. How the geometry of the confinement affects the opening and other structural parameters of DNA molecule is the objective of this manuscript. We have used a statistical model(PBD model) and Molecular dynamics simulations for our purpose. (c) 2022 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2023-01-27

Structural, spectroscopic, in silico, in vitro and DNA binding evaluations of tyrosyl-lysyl-threonine - Bicak, Bilge; Kecel Gunduz, Serda; Budama Kilinc, Yasemin; Imhof, Petra; Gok, Bahar; Akman, Gizem; Ozel, Aysen E. (Journal of Biomolecular Structure & Dynamics, 2021)
The main objective of the present study is to investigate the molecular structure and DNA binding interaction of the tyrosyl-lysyl-threonine (YKT) tripeptide, which has anticancer, antioxidant and analgesic properties, using various in silico (MD, QM, molecular docking), spectroscopic (UV, FT-IR, FTIR-ATR, Raman, gel electrophoresis) and in vitro (MCF-7 and HeLa cancer cell lines and BEAS-2B cell line) methods. The optimized geometry, vibrational wavenumbers, molecular electrostatic potential (MEP), natural bond orbital (NBO) and HOMO-LUMO (highest occupied molecular orbital- lowest unoccupied molecular orbital) calculations were carried out with Density Functional Theory (DFT) using B3LYP/6-311++G(d,p) basis set to indicate conformational, vibrational and intramolecular charge transfer characteristics. The assignment of all fundamental theoretical vibration wavenumbers was performed using potential energy distribution analysis (PED). DNA is a significant pharmacological target of drugs in several diseases such as cancer. For this reason, molecular docking calculation was used to elucidate the binding and interaction between YKT tripeptide and DNA at the atomic level. Also, the dynamic behaviors of YKT and DNA was examined using MD simulations. Besides, the interaction of YKT with DNA was experimentally examined by UV titration method and agarose gel electrophoresis method. Experimental results showed that YKT was intercalatively and electrostatically bound to CT-DNA (Calf thymus DNA) and cleavage pBR322 DNA in the presence of H2O2. The pharmacokinetic profile of YKT was also obtained. Cytotoxic effect of YKT was evaluated on MCF-7, HeLa and BEAS-2B cell lines. Hence, these studies about YKT tripeptide may pave the way for the development of various cancer drugs.
CRIS-Team WoS Importer:2021-09-10

Tacrine-sugar mimetic conjugates as enhanced cholinesterase inhibitors - Oliveira de Santana, Quelli Larissa; Santos Evangelista, Tereza C.; Imhof, Petra; Ferreira, Sabrina Baptista; Fernández-Bolaños, José G.; Sydnes, Magne O.; Lopéz, Óscar; Lindbäck, Emil (Organic & Biomolecular Chemistry, 2021)
We have used the Cu(i)-catalyzed azide-alkyne Huisgen cycloaddition reaction to obtain two families of bivalent heterodimers where tacrine is connected to an azasugar or iminosugar, respectively,vialinkers of variable length. The heterodimers were investigated as cholinesterase inhibitors and it was found that their activity increased with the length of the linker. Two of the heterodimers were significantly stronger acetylcholinesterase inhibitors than the monomeric tacrine. Molecular modelling indicated that the longer heterodimers fitted better into the active gorge of acetylcholinesterase than the shorter counterparts and the former provided more efficient simultaneous interaction with the tryptophan residues in the catalytic anionic binding site (CAS) and the peripheral anionic binding site (PAS).
CRIS-Team Scopus Importer:2021-04-02

The Effect of a G:T Mispair on the Dynamics of DNA - Imhof, Petra; Zahran, Mai (PLoS ONE, 2013)
Distortions in the DNA sequence such as damages or mispairs are specifically recognized and processed by DNA repair enzymes. A particular challenge for the enzymatic specificity is the recognition of a wrongly-placed native nucleotide such as thymine in T:G mispairs. An important step of substrate binding which is observed in many repair proteins is the flipping of the target base out of the DNA helix into the enzyme's active site. In this work we investigate how much the intrinsic dynamics of mispaired DNA is changed compared to canonical DNA. Our molecular dynamics simulations of DNA with and without T:G mispairs show significant differences in the conformation of paired and mispaired DNA. The wobble pair T:G shows local distortions such as twist, shear and stretch which deviate from canonical B form values. Moreover, the T:G mispair is found to be kinetically less stable, exhibiting two states with respect to base opening: a closed state comparable to the canonical base pairs, and a more open state, indicating a proneness for base flip. In addition, we observe that the thymine base in a T:G mispair is significantly more probable to be flipped than thymine in a T:A pair or cytosine in a C:G pair. Such local deformations and in particular the existence of a second, more-open state can be speculated to help the target-site recognition by repair enzymes. © 2013 Imhof, Zahran.
CRIS-Team Scopus Importer:2020-02-18

The vibrational spectrum of the hydrated alanine-leucine peptide in the amide region from IR experiments and first principles calculations - Hassan, Irtaza; Donati, Luca; Stensitzki, Till; Keller, Bettina G.; Heyne, Karsten; Imhof, Petra (Chemical Physics Letters, 2018)
We have combined infrared (IR) experiments with molecular dynamics (MD) simulations in solution at finite temperature to analyse the vibrational signature of the small floppy peptide Alanine-Leucine. IR spectra computed from first-principles MD simulations exhibit no distinct differences between conformational clusters of α-helix or β-sheet-like folds with different orientations of the bulky leucine side chain. All computed spectra show two prominent bands, in good agreement with the experiment, that are assigned to the stretch vibrations of the carbonyl and carboxyl group, respectively. Variations in band widths and exact maxima are likely due to small fluctuations in the backbone torsion angles.
CRIS-Team Scopus Importer:2020-02-18
Keywords: First-principles molecular dynamics simulations; Infrared spectra; Peptide

Umbrella sampling of proton transfer in a creatine-water system - Ivchenko, Olga; Bachert, Peter; Imhof, Petra (Chemical Physics Letters, 2014)
Proton transfer reactions are among the most common processes in chemistry and biology. Proton transfer between creatine and surrounding solvent water is underlying the chemical exchange saturation transfer used as a contrast in magnetic resonance imaging. The free energy barrier, determined by first-principles umbrella sampling simulations (EaDFT 3 kcal/mol) is in the same order of magnitude as the experimentally obtained activation energy. The underlying mechanism is a first proton transfer from the guanidinium group to the water pool, followed by a second transition where a proton is "transferred back" from the nearest water molecule to the deprotonated nitrogen atom of creatine. © 2014 The Authors.
CRIS-Team Scopus Importer:2020-02-18